2017
DOI: 10.1038/s41598-017-06847-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation signatures of chronic alcohol dependence in purified CD3+ T-cells of patients undergoing alcohol treatment

Abstract: Several studies have shown an association of alcohol dependence with DNA methylation (DNAm), suggesting that environmentally-induced changes on epigenomic variation may play an important role in alcohol dependence. In the present study, we analysed genome-wide DNAm profiles of purified CD3+ T-cells from pre- and post-treatment alcohol dependent patients, as well as closely matched healthy controls. We identified 59 differentially methylated CpG sites comparing patients prior to treatment with healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Additionally, alcohol is a potent agent, and the observed differences between patients and controls may demonstrate the strong effect of alcohol consumption, an effect which is reduced after cessation of drinking but continues to be observable long afterwards . In particular, our results are in line with studies showing pronounced differences between patients in acute withdrawal and after 2 weeks of recovery .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, alcohol is a potent agent, and the observed differences between patients and controls may demonstrate the strong effect of alcohol consumption, an effect which is reduced after cessation of drinking but continues to be observable long afterwards . In particular, our results are in line with studies showing pronounced differences between patients in acute withdrawal and after 2 weeks of recovery .…”
Section: Discussionsupporting
confidence: 90%
“…They show that the degree of DNAm diminishes after a 30‐day in‐patient treatment program. Another EWAS further included a comparison of DNAm changes in 24 patients prior to and after a 3‐week detoxification program and 23 controls . At a DNAm difference of > 5%, 59 CpG sites were differentially methylated between patients and controls before entering the treatment program and 48 CpG sites were differentially methylated comparing patients before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the differentially methylated cytosines identified between controls and alcohol-dependent subjects were reversed during abstinence to levels similar to controls. Similarly, Bruckmann et al (Bruckmann et al 2017) found that some of the differentially methylated cytosines identified in CD3+ T cells between healthy controls and alcohol-dependent patients reverted back to control levels after abstinence, demonstrating a potential causal role for alcohol in changing DNAm in blood cells.…”
Section: Epigenetic Modifiersmentioning
confidence: 89%
“…In a longitudinal study of 165 female participants, different degrees of alcohol consumption over the past 6 months were found to be associated with two loci reaching epigenome-wide significance [37]. Another EWAS compared methylation patterns in 24 patients before and after a 3-week detoxification program and 23 controls [38]. Here, 59 CpG sites were differentially methylated between patients and controls before entering the treatment program and 48 CpG sites were differentially methylated comparing patients before and after treatment [38].…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“…Another EWAS compared methylation patterns in 24 patients before and after a 3-week detoxification program and 23 controls [38]. Here, 59 CpG sites were differentially methylated between patients and controls before entering the treatment program and 48 CpG sites were differentially methylated comparing patients before and after treatment [38].…”
Section: Epigenetic Factorsmentioning
confidence: 99%